2016
DOI: 10.1186/s12967-015-0755-y
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of human myeloid-derived suppressor cells after blood draw

Abstract: BackgroundHuman myeloid-derived suppressor cells (MDSC) have been described as a group of immature myeloid cells which exert immunosuppressive action by inhibiting function of T lymphocytes. While there is a huge scientific interest to study these cells in multiple human diseases, the methodological approach varies substantially between published studies. This is problematic as human MDSC seem to be a sensible cell type concerning not only cryopreservation but also time point after blood draw. To date data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…We found that in contrast to blood samples separated by Ficoll density gradient (fresh or cryopreserved/thawed), only cryopreservation/thawing of the whole-blood sample preserves the levels of CD33þCD11bþHLA-DR À MDSCs as detected in fresh samples. These results are supported by previous studies showing that fresh or cryopreserved/thawed PBMCs, isolated on Ficoll density gradient, showed significantly modified frequencies of both CD33 þ CD11b þ HLA-DR À and CD15 þ LIN À HLA-DR À MDSC populations as compared with their profile in the whole fresh blood sample (22,23). It is important to note that in the process of the Ficoll density gradient separation step, due to the distribution of the different leukocyte populations, cells such as granulocytic MDSCs are neglected (missed) and only PBMCs containing the monocytic MDSCs are taken.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We found that in contrast to blood samples separated by Ficoll density gradient (fresh or cryopreserved/thawed), only cryopreservation/thawing of the whole-blood sample preserves the levels of CD33þCD11bþHLA-DR À MDSCs as detected in fresh samples. These results are supported by previous studies showing that fresh or cryopreserved/thawed PBMCs, isolated on Ficoll density gradient, showed significantly modified frequencies of both CD33 þ CD11b þ HLA-DR À and CD15 þ LIN À HLA-DR À MDSC populations as compared with their profile in the whole fresh blood sample (22,23). It is important to note that in the process of the Ficoll density gradient separation step, due to the distribution of the different leukocyte populations, cells such as granulocytic MDSCs are neglected (missed) and only PBMCs containing the monocytic MDSCs are taken.…”
Section: Discussionsupporting
confidence: 86%
“…1C-D). These results are supported by previous studies showing that PBMC isolation using Ficoll before and after freezing, significantly changes the frequencies of both CD33 þ CD11b þ HLA-DR À and CD15 þ LIN À HLA-DR À MDSC populations after sample are thawed (22,23).…”
Section: Patientssupporting
confidence: 88%
“…Several studies have emphasized on the significance of sample handling and processing when monitoring MDSC levels in circulation and are in agreement over the adverse effects of cryopreservation and the delayed time points at which MDSC analysis was carried out following blood collection [2022]. Mandruzzato et al suggested to perform analysis on fresh blood to prevent possible loss of some MDSC subsets mainly G-MDSC.…”
Section: Discussionmentioning
confidence: 99%
“…One of the critical reasons is the heterogeneity of MDSC testing among different centres . At present, the standard method to separate MDSC is by density gradient centrifugation only in peripheral blood (PB) . This testing technology is not easily standardized between laboratories, which might be a critical cause of the heterogeneity of results in MDSC‐targeted studies.…”
Section: Introductionmentioning
confidence: 99%